A neveléstudomány nemzetközi modelljei és tudományos irányzatai - Németh, András (Magyar Pedagógia, 2015)
This article aims at reviewing and analyzing the emergence of Educational Sciences and their recent influential paradigms. As an introduction, the article focuses on the major findings from the sociology of knowledge oriented research that had grounded the shifts in researching the history of Educational Sciences. Drawing on this basis, the following sections of the article examine the trends in Educational Sciences from three aspects. First, an analysis of macro level processes in European science development is presented, which influenced Educational Sciences, as well as the epistemological paradigms informing these processes. Second, there follows a description of the emerging historic-regional developmental models (English-American, French, and German) of the academic institutionalization of Educational Sciences at the universities. This process was taking shape in parallel with the professionalization of the intellectuals. The centre of the article is a detailed historic description and synthesis. On the one hand, this briefly presents scientific paradigms relevant to Educational Sciences; on the other hand, it gives an overview of schools of educational thinking and their international reception determining recent academic discourses worldwide.